2011
DOI: 10.1590/s0037-86822011005000025
|View full text |Cite
|
Sign up to set email alerts
|

Aedes aegypti and Aedes albopictus (Diptera: Culicidae): coexistence and susceptibility to temephos, in municipalities with occurrence of dengue and differentiated characteristics of urbanization

Abstract: Aedes aegypti and Aedes albopictus (Diptera: Culicidae): coexistence and susceptibility to temephos, in municipalities with occurrence of dengue and differentiated characteristics of urbanizationAedes aegypti e Aedes albopictus (Diptera: Culicidae): coexistência e suscetibilidade ao temephos, em municípios com ocorrência de casos de dengue e diferentes características de urbanização

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 18 publications
1
20
0
2
Order By: Relevance
“…Entretanto, em diferentes partes do mundo e no Brasil, tem sido registrada resistência desse díptero aos inseticidas convencionais (FURTADO et al, 2005;PROPHIRO et al, 2008;PORTO et al, 2008;PROPHIRO et al, 2011).…”
Section: Introductionunclassified
“…Entretanto, em diferentes partes do mundo e no Brasil, tem sido registrada resistência desse díptero aos inseticidas convencionais (FURTADO et al, 2005;PROPHIRO et al, 2008;PORTO et al, 2008;PROPHIRO et al, 2011).…”
Section: Introductionunclassified
“…This is appropriate since yearly changes in susceptibility of various mosquitoes species which have become resistant worldwide to chemical insecticides (Seccacini et al 2008;KerahHinzoumbé et al 2008;Marcombe et al 2009;Sarkar et al 2009;Yewhalaw et al 2011;Prophiro et al 2011) are reported.…”
Section: Introductionmentioning
confidence: 99%
“…Maruim, 30km from of the capital, had the highest number of eggs, 21,896, and Canindé de São Francisco, 213km from the capital, had the lowest number of eggs, 2,302 eggs. This difference in infestation level could be related to the demographic density of the cities, as cities near the capital had a high number of inhabitants per km 2 and most of these cities are interconnected. Crowded places often have a wide availability of containers with conditions suited to the development of mosquitoes and are devoid of geographical barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical insecticides are still widely used in vector control programs, despite selection for resistant populations of Aedes aegypti and Aedes albopictus, which threatens the effectiveness of control programs 2 .…”
Section: Introductionmentioning
confidence: 99%